Effects of external static electrical field on thermal and electrical conductivity in the Al-Cu, Al-Ni, and Al-Si eutectic alloys - Basit, Sercan; Esener, Pinar Ata; Aydogan, Yigit Yavuz; Aksoz, Sezen; Marasli, Necmettin (ELSEVIER, 2024)
This study aims to investigate the effects of external positive and negative static electric fields (E+ and Erespectively) on thermal conductivity (K) and electrical conductivity (a) in Al-33 wt. % Cu, Al-6.4 wt. % Ni and Al-12 wt. % Si eutectic alloys. For this purpose, the solidifications of Al-Cu, Al-Ni, and Al-Si eutectic alloys were directionally done under E+ and E-. The directions of E were chosen to be parallel (E+) and antiparallel (E-) to the solid-liquid (S-L) growth direction and the magnitudes of E were approximately (+10) and (_ 10) kV cm_ 1 and (+16) and (-16) kV cm_ 1 for the Al-Cu, Al-Ni, and Al-Si eutectic alloys, respectively. The effects of E+ and E_ on the K and a were determined by the longitudinal heat flow and the four-point probe methods, respectively. While the K and a values decreased with increasing temperature, the K and a were increased and decreased with E+ and E_, respectively.
Keywords: Eutectic alloys; Solidification under electric field; Thermal conductivity; Electrical conductivity; SN TERNARY ALLOY; MAGNETIC-FIELD; MICROINDENTATION HARDNESS; MICROSTRUCTURE; TEMPERATURE; SOLIDIFICATION; GRADIENT; GROWTH; Thermodynamics; Chemistry